2012
DOI: 10.1212/wnl.0b013e318275978c
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based guideline update: Steroids and antivirals for Bell palsy

Abstract: Objective: To review evidence published since the 2001 American Academy of Neurology (AAN) practice parameter regarding the effectiveness, safety, and tolerability of steroids and antiviral agents for Bell palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
127
1
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 16 publications
0
127
1
16
Order By: Relevance
“…35 A recent update of this guideline advocated the use of corticosteroids and concluded that antivirals may be of modest benefit. 36 Of two other treatment guidelines, one concluded that there was insufficient evidence to give corticosteroids to children 37 and the other suggested use of corticosteroids on the basis of a narrative review of the available evidence. 38 The present guideline used the GRADE methodology and offers recommendations addressing nonmedical therapeutic options that have been omitted from other guidelines.…”
Section: Other Guidelinesmentioning
confidence: 99%
“…35 A recent update of this guideline advocated the use of corticosteroids and concluded that antivirals may be of modest benefit. 36 Of two other treatment guidelines, one concluded that there was insufficient evidence to give corticosteroids to children 37 and the other suggested use of corticosteroids on the basis of a narrative review of the available evidence. 38 The present guideline used the GRADE methodology and offers recommendations addressing nonmedical therapeutic options that have been omitted from other guidelines.…”
Section: Other Guidelinesmentioning
confidence: 99%
“…According to the 2001 AAN use of acyclovir alone is not effective for the treatment of Bell palsy and that therapy with this agent is only possibly effective in facial recovery. [26] According to the academy's 2012 guidelines, benefit from antivirals has not been established 27,28 . In an analysis by`Quant et al, the routine use of antiviral agents was not warranted and the study recommended that newer antiviral agents may prove more beneficial than older antiviral agents used in the studies analyzed to date 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are offered them in addition to corticosteroids should be counselled that the increase in recovery is less than 7%. 16 A Cochrane review in 2015 found that antivirals combined with corticosteroids improved rates of incomplete recovery compared with corticosteroids alone, but this was not significant and the evidence was low quality. There was moderate-quality evidence that the combination reduced long-term sequelae such as excessive tear production and synkinesis.…”
Section: Conflict Of Interest: None Declaredmentioning
confidence: 99%